Analysis of methodologies for the calculation of nuclear conductors (2009)
In  this  paper,  the  authors  present  the most  important  considerations,  achievements  and  contributions  that  they achieve  through  the  experimental  and  theoretic  analysis  that  they  did  about  the methodologies  to  estimate  the Ampacity Rating  in Overhead conductors  propose  to  IEEE  and CIGRÉ  investigation  groups. Additionally  the authors present an analysis about the application of these methodologies in the Colombian’s electrical service.